Nominal and Relative Clauses in Online Book Reviews - Racková, Kateřina (Univerzita Pardubice, 2025)
This thesis examines the distribution of nominal and relative clauses in online book reviews. The theoretical part of the thesis introduces the topic of subordination and provides a detailed description of nominal and relative clauses, focusing on their form, function and more elaborate classification of each clause type. Lastly, the genre of book reviews is defined with respect to its main discourse functions, typical structure and linguistic features. The practical part presents an in-depth analysis of the corpus of nominal and relative clauses from a selection of book reviews. The analysis aims to outline the most prevailing forms and functions of the collected nominal and relative clauses, and the findings are interpreted in the context of the book review genre and its discourse functions.
Obsahové a vztažné věty vedlejší v online knižních recenzích
Keywords: nominal clause; relative clause; subordination; subordinate clause; book review; syntax; obsahová věta; vztažná věta; subordinace; vedlejší věta; knižní recenze; syntax